(untitled) (Studia austriaca, 2024)
The essay examines the ferrotypes taken in the Wiener Prater, featuring members of ‘Jung-Wien’, including Hermann Bahr, Richard Beer-Hofmann, Hugo von Hofmannsthal, Felix Salten, and Arthur Schnitzler. A closer examination is given to one photo, revealing that contrary to common belief, the figure depicted is not Hofmannsthal, but rather the industrialist Fritz Mendl (1864–1929).